2022
DOI: 10.1021/acsami.2c12266
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles-Based Quantum Transport Simulations of High-Performance and Low-Power MOSFETs Based on Monolayer Ga2O3

Abstract: The electronic properties of monolayer (ML) Ga2O3 and transport properties of ML Ga2O3-based n-type metal–oxide–semiconductor field-effect transistors (MOSFETs) are investigated by first-principles calculations under the framework of density functional theory (DFT) coupled with the nonequilibrium Green’s function (NEGF) formalism. The results show that ML Ga2O3 has a quasi-direct band gap of 4.92 eV, and the x- and y-directed electron mobilities are 1210 and 816 cm2 V–1 s–1 at 300 K, respectively, under the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…For 3 nm devices, the ON-to-OFF current ratio is observed to be more than 4 decades, which is remarkable. As most of the 2D material-based transistors in the literature are simulated with relaxed OFF current criteria ( I OFF = 100 nA/μm), we are able to compare our results with only a few other studies. ,− The I ON for CP1 borophene MOSFETs is well balanced compared to the transistors based on monolayer β-TeO 2 and SiP; however, the 12 nm monolayer GeC-based transistor shows comparatively balanced I ON . On the other hand, for L CH = 5 nm, I ON of CP1 borophene MOSFET is more nicely balanced than that of Zr–Zr–C–O–O and Ti–Zr–C–O–O Schottky barrier transistors.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…For 3 nm devices, the ON-to-OFF current ratio is observed to be more than 4 decades, which is remarkable. As most of the 2D material-based transistors in the literature are simulated with relaxed OFF current criteria ( I OFF = 100 nA/μm), we are able to compare our results with only a few other studies. ,− The I ON for CP1 borophene MOSFETs is well balanced compared to the transistors based on monolayer β-TeO 2 and SiP; however, the 12 nm monolayer GeC-based transistor shows comparatively balanced I ON . On the other hand, for L CH = 5 nm, I ON of CP1 borophene MOSFET is more nicely balanced than that of Zr–Zr–C–O–O and Ti–Zr–C–O–O Schottky barrier transistors.…”
Section: Resultsmentioning
confidence: 86%
“…The combined DFT-NEGF (non-equilibrium Green’s function)-based methodology, such as the one implemented in the QuantumATK package, has become prominent for exploring 2D material-based transistor characteristics. However, this methodology can become computationally prohibitively expensive when employed with hybrid functionals such as HSE. Apart from that, the Brillouin zone of clustered-P1 borophene, shown in Figure d, is not orthogonal, and QuantumATK is not adaptable to such crystal structures.…”
Section: Resultsmentioning
confidence: 99%
“…37 However, the I−V g curves of Ga 2 O 3 MOSFETs with L g = 5 nm are almost identical whether the phonon scattering is considered or not. 38 Therefore, here, we only consider ballistic transport to simulate the I−V g transfer characteristics of ML WSi 2 N 4 MOSFETs at the ultrashort scale.…”
Section: ■ Simulation Methodsmentioning
confidence: 99%
“…For example, it was reported that the current of ML BP transistors with the 10.5 nm gate length can be up to 95% of its ballistic transport limitation . However, the I–V g curves of Ga 2 O 3 MOSFETs with L g = 5 nm are almost identical whether the phonon scattering is considered or not . Therefore, here, we only consider ballistic transport to simulate the I–V g transfer characteristics of ML WSi 2 N 4 MOSFETs at the ultrashort scale.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…As a representative, 2D Ga 2 O 3 has received extensive research and attention for next-generation high-performance (HP) and low-power (LP) field-effect transistors (FETs). Previous study has demonstrated that the on-current (I on ) of monolayer (ML) Ga 2 O 3 FET for HP application is as high as 2890 µA µm −1 , which is more than the most reported 2D semiconducting materials [10]. The delay time (τ ) as well as the power delay product (PDP) can meet the demands of the latest International Technology Roadmap for Semiconductors (ITRSs) for HP and LP applications, and outperform the current of Si-based FETs [10].…”
Section: Introductionmentioning
confidence: 98%